Airway disease: a confusion inside an enigma. Issue 4 (12th December 2022) - Morice, Alyn H.
The classification of airway disease is in a mess. When I was a medical student and dinosaurs walked the earth, there were four conditions: childhood asthma, late-onset asthma, chronic bronchitis, and emphysema. The latter two were then amalgamated, for reasons I still do not understand, into COPD, and defined on the basis of fixed airflow obstruction on spirometry. The two forms of asthma had similarities in that they had variable airflow obstruction and were steroid responsive. Childhood asthma was characterised by atopy, family history, and associated conditions such as eczema and rhinitis. Late-onset asthma rarely had these associations. Current diagnostic categories of airway disease are conflicting and contradictory. Historically, we were reliant on airway physiology. However, pathology is the study of disease. A reappraisal is necessary. https://bit.ly/3CZSqiQ